Educational inequalities in mortality of patients with atrial fibrillation in Norway. (4th March 2017) - Akerkar, Rupali; Ebbing, Marta; Sulo, Gerhard; Ariansen, Inger; Igland, Jannicke; Tell, Grethe S.; Egeland, Grace M.
Abstract: Objectives: We explored the educational gradient in mortality in atrial fibrillation (AF) patients. Design: We prospectively followed patients hospitalized with AF as primary discharge diagnosis in the Cardiovascular Disease in Norway 2008-2012 project. The average length of follow-up was 2.4 years. Mortality by educational level was assessed by Cox proportional hazard models. Population attributable fractions (PAF) were calculated. Analyses stratified by age (≤75 and >75 years of age), and adjusted for age, gender, medical intervention, and Charlson Comorbidity Index. Results: Of 42, 138 AF patients, 16% died by end of 2012. Among younger patients, those with low education (≤10 years) had a HR of 2.3 (95% confidence interval 2.0, 2.6) for all-cause mortality relative to those with any college or university education. Similar results were observed for cardiovascular mortality. Disparities in mortality were greater among younger than older patients. A PAF of 35.9% (95% confidence interval 27.9, 43.1) was observed for an educational level of high school/vocational school or less versus higher education in younger patients. Conclusions: Increasing educational level associated with better prognosis suggesting underlying education-related behavioral and medical determinants of mortality. A considerable proportion of mortality within 5 years following hospital discharge could be prevented.